2017
DOI: 10.3892/ol.2017.7255
|View full text |Cite
|
Sign up to set email alerts
|

Ampelopsin‑induced reactive oxygen species enhance the apoptosis of colon cancer cells by activating endoplasmic reticulum stress‑mediated AMPK/MAPK/XAF1 signaling

Abstract: Abstract. Ampelopsin (Amp) is bioactive natural product and exerts anti-cancer effects against several cancer types. The present study investigated the anti-colon cancer activity of Amp and explored its mechanism of action. The treatment of colon cancer cells with Amp resulted in the dose-and time-dependent induction of apoptosis via the activation of endoplasmic reticulum (ER) stress, 5' adenosine monophosphate-activated protein kinase (AMPK), and c-Jun N-terminal protein kinase (JNK)/p38 mitogen-activated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…The relationships among ER stress, autophagy and ROS are rather complicated. Several studies showed that ER stress and autophagy were stimulated by the production of ROS 43 , 44 . However, the increasing number of studies has illustrated that ER stress and autophagy could disrupt the delicate balance between ROS production and degradation 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationships among ER stress, autophagy and ROS are rather complicated. Several studies showed that ER stress and autophagy were stimulated by the production of ROS 43 , 44 . However, the increasing number of studies has illustrated that ER stress and autophagy could disrupt the delicate balance between ROS production and degradation 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Salubrinal pretreatment effectively attenuated Ampelopsin-induced phosphorylation of p38-MAPK and JNK (42). Additionally, ER stress inhibition markedly reduced the Ampelopsindependent phosphorylation of AMPK and expression of XAF1 (XIAP-Associated Factor-1) in colon cancer cells (42). Overall these findings clearly showcased that Ampelopsin induced apoptotic death in colon cancer cells through ER stress-driven AMPK/MAPK/XAF1 signaling axis.…”
Section: Er Stressmentioning
confidence: 71%
“…Ampelopsin induced an increase in phosphorylated levels of p38-MAPK and JNK. Salubrinal pretreatment effectively attenuated Ampelopsin-induced phosphorylation of p38-MAPK and JNK (42). Additionally, ER stress inhibition markedly reduced the Ampelopsindependent phosphorylation of AMPK and expression of XAF1 (XIAP-Associated Factor-1) in colon cancer cells (42).…”
Section: Er Stressmentioning
confidence: 99%
“…The highly elevated pro-oxidant capability of Botrytis wines was firstly observed and described by Sipka and coworkers [16]; in addition, the anti-oxidant capacity of Aszú wines was found to be much less than that of red wines (not published observation, Sipka, 2019). (b) The remarkably higher amounts of iron (Fe 2+ 6-18 mg/L) occurring in all these wines compared to those in red wines (2.0-3.0 mg/L) [3] could react with H 2 O 2 (e.g., in the Fenton reaction) and could induce an increased production of reactive oxygen species (ROS) leading to apoptosis in colon cancer cells [17]. Additionally, H 2 O 2 could stimulate the natural killer cells attacking the tumor cells [18].…”
Section: Discussionmentioning
confidence: 99%